Bankers' Communication Know-how: An Analysis from Commercial Banks of Kathmandu valley (Quest Journal of Management and Social Sciences, 2020)
Background: In the modern era, communication has changed the way of working styles, banking sectors are practicing banking communication in order to make work easier, faster, comfortable and accurate. Banking communication plays the role of mediator in between bank, customer, government, shareholder, suppliers, client, board of directors and employees which strengthen connection between them. Therefore, banker's experience on banking communication enhances banking system, employee's behavior and core banking service facilities management.Objective: This study analyses socio demographic, financial service management, human resource management, corporate influence, organizational regulator, communication culture, responsiveness, organizational culture, e-banking service facilities, organizational functioning and communication encounters.Methodology: This study is based on exploratory research design showing causal relationship between latent and observed variables. The research prepares systematic questionnaire to interview respondents where 355 employees are interviewed by using purposive sampling technique. The result is based on descriptive analysis and Awareness Index.Results: The Employees Awareness Index depicts 12% of employees are inadequately aware about banking communication followed by 46% of employees are moderately aware and 37% of employees are adequately aware about banking communication.Conclusion: This study revealed that, in order to improve banking system, the bank should focus on financial service management and organizational regulator. For smooth control on employee's behavior bank should concentrate on communication culture, responsiveness and organizational culture. Similarly, core banking service facilities management should overview on e-banking service facilities.Originality: This paper is original and not published anywhere else.